Aldosterone induces active K(+) secretion by enhancing mucosal expression of Kcnn4c and Kcnma1 channels in rat distal colon - Singh, Satish K. (American Physiological Society, 2012)
Although both Kcnn4c and Kcnma1 channels are present on colonic mucosal membranes, only Kcnma1 has been suggested to mediate K(+) secretion in the colon. Therefore, studies were initiated to investigate the relative roles of Kcnn4c and Kcnma1 in mediating aldosterone (Na-free diet)-induced K(+) secretion. Mucosal to serosal (m-s), serosal to mucosal (s-m), and net (86)Rb(+) (K(+) surrogate) fluxes as well as short circuit currents (I(sc); measure of net ion movement) were measured under voltage clamp condition in rat distal colon. Active K(+) absorption, but not K(+) secretion, is present in normal, while aldosterone induces active K(+) secretion (1.04 ± 0.26 vs. −1.21 ± 0.15 μeq·h(−1)·cm(−2); P < 0.001) in rat distal colon. Mucosal VO(4) (a P-type ATPase inhibitor) inhibited the net K(+) absorption in normal, while it significantly enhanced net K(+) secretion in aldosterone animals. The aldosterone-induced K(+) secretion was inhibited by the mucosal addition of 1) either Ba(2+) (a nonspecific K(+) channel blocker) or charybdotoxin (CTX; a common Kcnn4 and Kcnma1 channel blocker) by 89%; 2) tetraethyl ammonium (TEA) or iberiotoxin (IbTX; a Kcnma1 channel blocker) by 64%; and 3) TRAM-34 (a Kcnn4 channel blocker) by 29%. TRAM-34, but not TEA, in the presence of IbTX further significantly inhibited the aldosterone-induced K(+) secretion. Thus the aldosterone-induced Ba(2+)/CTX-sensitive K(+) secretion consists of IbTX/TEA-sensitive (Kcnma1) and IbTX/TEA-insensitive fractions. TRAM-34 inhibition of the IbTX-insensitive fraction is consistent with the aldosterone-induced K(+) secretion being mediated partially via Kcnn4c. Western and quantitative PCR analyses indicated that aldosterone enhanced both Kcnn4c and Kcnma1α protein expression and mRNA abundance. In vitro exposure of isolated normal colonic mucosa to aldosterone also enhanced Kcnn4c and Kcnma1α mRNA levels, and this was prevented by exposure to actinomycin D (an RNA synthesis inhibitor). These observations indicate that aldosterone induces active K(+) secretion by enhancing mucosal Kcnn4c and Kcnma1 expression at the transcriptional level.